Cronobacter sakazakii ATCC 29544 Translocated Human Brain Microvascular Endothelial Cells via Endocytosis, Apoptosis Induction, and Disruption of Tight Junction - Jin, Tong; Guan, Ning; Du, Yuhang; Zhang, Xinpeng; Li, Jiahui; Xia, Xiaodong (Frontiers in Microbiology, 2021)
Cronobacter sakazakii (C. sakazakii) is an emerging opportunistic foodborne pathogen that can cause neonatal necrotizing enterocolitis, meningitis, sepsis in neonates and infants with a relatively high mortality rate. Bacterial transcytosis across the human brain microvasular endothelial cells (HBMEC) is vital for C. sakazakii to induce neonatal meningitis. However, there are few studies focusing on the mechanisms by which C. sakazakii translocates HBMEC. In this study, the translocation processes of C. sakazakii on HBMEC were explored. C. sakazakii strains could effectively adhere to, invade and intracellularly survive in HBMEC. The strain ATCC 29544 exhibited the highest translocation efficiency across HBMEC monolayer among four tested strains. Bacteria-contained intracellular endosomes were detected in C. sakazakii-infected HBMEC by a transmission electron microscope. And endocytosis-related proteins CD44, Rab5, Rab7, LAMP2 were increased after infection, while the level of Cathepsin L did not change. C. sakazakii induced TLR4/NF-κB inflammatory signal pathway activation in HBMEC, with increased NO production and elevated mRNA levels of IL-8, IL-6, TNF-α, IL-1β, iNOS and COX-2. C. sakazakii infection also caused LDH release, caspase-3 activation and HBMEC apoptosis. Meanwhile, increased Dextran-FITC permeability and decreased trans epithellal electric resistance indicated that C. sakazakii disrupted tight junction of HBMEC monolayers, which was confirmed by decreased level of tight junction-related proteins ZO-1 and Occludin. These findings suggest that C. sakazakii induced intracellular bacterial endocytosis, stimulated inflammation and apoptosis, disrupted monolayer tight junction in HBMEC, which all together contribute to bacterial translocation.